Distribution of Diaphorina citri, a citrus huanglongbing vector in Indonesia and new locality records - Haris Setyaningrum; Edhi Martono; Jianhua Mo; Siti Subandiyah; Tri Joko; Alan Soffan (Universitas Lampung, 2026)
The Asiatic citrus psyllid (Diaphorina citri) is the primary vector of the destructive citrus disease huanglongbing (HLB), posing a significant threat to citrus production in Indonesia. Systematic surveys of D. citri are essential for identifying areas at high risk of HLB outbreaks and for supporting sustainable disease management. This study aimed to assess the population distribution of D. citri in major citrus-producing regions of Indonesia and to evaluate its potential risk for HLB spread. The research was conducted over two consecutive years (2022–2023) across key citrus production areas on the islands of Java, Sumatra, Kalimantan, and Bali. A total of 206 sampling sites were surveyed using direct manual inspection and two types of yellow traps. D. citri was detected at 35 locations, representing new country records. The distribution pattern was relatively uniform in Sumatra but more scattered in Java and Kalimantan, with the highest population densities observed in the lowland areas of Bengkulu. These findings provide critical insights into D. citri distribution patterns and support targeted surveillance and sustainable management strategies to mitigate the impact of HLB in Indonesia.